Ultra-low adhesion coating with anti-sticking and self-bleeding properties, and preparation method and application thereof

CN119192996BActive Publication Date: 2026-10-27NORTHWESTERN POLYTECHNICAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411598630.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2026-10-27
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

[0004]然而,当前的自渗油表面制备方法通常涉及复杂的多步工艺,例如多孔结构的构筑、润滑液的注入和保持等

Benefits of technology

1. 简单高效的一步涂覆工艺:本发明采用一步涂覆工艺,将防粘、自渗油和高附着力等多种功能集成于单一涂层中。这种方法显著简化了传统多层涂覆工艺,大幅降低了生产成本和时间。同时,一步涂覆还减少了层间界面问题,提高了涂层的整体性能和稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192996B_ABST
    Figure CN119192996B_ABST
Patent Text Reader

Abstract

The present disclosure provides an ultra-low adhesion coating with anti-sticking and self-oil-bleeding properties, a preparation method and application thereof. The preparation method of the ultra-low adhesion coating comprises the following steps: cleaning the surface of a substrate; preparing a coating mixture containing a self-oil-bleeding component: mixing a vinyl-terminated polydimethylsiloxane prepolymer, a hydrogen-containing silicone oil, a low molecular weight dimethyl silicone oil and a platinum catalyst in a certain proportion, stirring, degassing in a vacuum environment, and curing to form an ultra-low adhesion coating with anti-sticking and self-oil-bleeding properties. The preparation method is simple, can form an ultra-low adhesion coating with anti-sticking and self-oil-bleeding properties on the surface of various substrates, and has high adhesion with the substrate. In addition, the silicone rubber adhesion method based on the coating significantly improves the bonding force of the silicone rubber and the substrate, effectively improves the production efficiency, reduces the production cost, and has good industrial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional coating materials technology, specifically to ultra-low adhesion coatings with anti-stick and self-oiling properties, their preparation methods, and applications. Background Technology

[0002] Anti-stick coatings have wide applications in industry, medicine, food processing, and marine engineering, such as preventing adhesion, reducing friction, facilitating cleaning, and reducing biofouling. Currently, superhydrophobic coatings and low surface energy materials are widely used to achieve anti-stick effects. These coatings typically reduce surface energy by constructing micro / nano structures on the substrate surface or introducing fluoropolymers, thereby reducing material adhesion. However, traditional superhydrophobic coatings have some limitations in practical applications. First, the micro / nano structures of these coatings are susceptible to mechanical damage, leading to a decrease in anti-stick performance. Second, the use of fluoropolymers may raise environmental and health concerns. Furthermore, most anti-stick coatings have insufficient adhesion to the substrate surface, making them prone to peeling off and affecting their long-term use.

[0003] To overcome the shortcomings of superhydrophobic coatings, slickin-wetting surfaces (SLIPS) have been proposed and attracted widespread attention. SLIPS effectively inhibit material adhesion by introducing lubricating fluid into a porous structure, forming a stable liquid thin layer. SLIPS exhibit excellent anti-stick and self-lubricating properties, and also possess a certain degree of self-repair capability for surface damage.

[0004] However, current methods for preparing self-oiling surfaces typically involve complex multi-step processes, such as the construction of porous structures, lubricant injection, and retention. These methods are often complex, costly, and inefficient. Furthermore, lubricant loss and evaporation can lead to a decline in anti-stick properties over time. On the other hand, how to improve coating adhesion to the substrate while maintaining anti-stick and self-oiling properties remains a pressing technical problem.

[0005] Therefore, there is an urgent need for a simple and efficient coating preparation method that can impart non-stick and self-oiling properties to materials, as well as high adhesion, to meet the needs of practical applications. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a simple and efficient coating preparation method that can construct an ultra-low adhesion coating with both anti-stick and self-oiling properties, and the coating has high adhesion to the substrate, thus meeting the needs of practical applications.

[0007] According to the present invention, a method for preparing an ultra-low adhesion coating with anti-stick and self-oiling properties is provided, comprising the following steps: Substrate pretreatment: Cleaning the surface of the substrate; Preparation of coating mixture containing self-exuding oil components: Vinyl-terminated polydimethylsiloxane prepolymer, hydrogen-containing silicone oil, platinum catalyst and low molecular weight dimethyl silicone oil are mixed in proportion, and a uniform coating mixture is obtained after stirring. After vacuum degassing, a uniform coating mixture containing self-exuding oil components is obtained. Applying an ultra-low adhesion self-exuding coating: After applying a coating mixture containing self-exuding oil components to the pretreated substrate surface, place it in an oven and cure it at 60-150℃ for 30-120 minutes to form an ultra-low adhesion coating on the substrate surface that has both anti-stick and self-exuding properties.

[0008] As a further explanation of the present invention, during the substrate pretreatment process, the substrate is ultrasonically cleaned sequentially with acetone, anhydrous ethanol and deionized water for 5 to 15 minutes each time to remove surface oil and impurities, and then dried in a clean environment for later use.

[0009] As a further explanation of the present invention, in the process of preparing the coating mixture containing self-penetrating oil components, the vinyl-terminated polydimethylsiloxane prepolymer and the hydrogen-containing silicone oil are mixed at a mass ratio of 100:(8-12). After adding a small amount of platinum catalyst and mixing evenly, the low molecular weight dimethyl silicone oil is added. The mass fraction of the low molecular weight dimethyl silicone oil in the coating mixture is 30%-70%. The molecular weight of the vinyl-terminated polydimethylsiloxane prepolymer is 5,000-20,000 g / mol. The hydrogen content of the hydrogen-containing silicone oil is 0.5-2.0 mmol / g. The platinum content of the platinum catalyst is 0.1-2 wt%. The viscosity of the low molecular weight dimethyl silicone oil is 5-200 cSt.

[0010] As a further explanation of the present invention, in the process of preparing the coating mixture containing self-penetrating oil components, the stirring temperature is 20-40°C, the stirring time is 0.5-2 hours, the vacuum degree of vacuum degassing is 1-100 Pa, and the degassing time is 10-60 minutes.

[0011] As a further explanation of the present invention, the coating method used in the process of coating the ultra-low adhesion self-oiling coating is one of spin coating, spray coating, blade coating, dip coating or screen printing. During the process of applying the coating mixture containing self-penetrating oil components to the surface of the pretreated substrate, the substrate is placed in an environment with a vacuum degree of 1~100Pa for degassing for 5~30 minutes before coating; the thickness of the coating after coating is 5~100μm.

[0012] As a further explanation of the present invention, the material of the substrate is one of stainless steel, aluminum alloy, glass, ceramic, silicon wafer, polycarbonate, polypropylene or polyimide.

[0013] The present invention also provides an ultra-low adhesion coating with anti-stick and self-oiling properties prepared by the above method.

[0014] The present invention also provides the application of the above-mentioned ultra-low adhesion coating with anti-stick and self-oiling properties in improving the adhesion of silicone rubber coatings.

[0015] As a further illustration of the present invention, an ultra-low adhesion coating with anti-stick and self-oiling properties is introduced between the substrate and the silicone rubber coating.

[0016] As a further explanation of the present invention, in the process of introducing an ultra-low adhesion coating between the substrate and the silicone rubber coating, a coating mixture containing self-exuding oil components is first coated onto the pretreated substrate surface with a coating thickness of 5-50 μm. After degassing under a vacuum of 1-100 Pa for 5-30 minutes, the coating is cured at 60-150°C for 1-15 minutes to obtain an interface layer containing self-exuding oil components. Subsequently, a silicone rubber material with a thickness of 5-100 μm is coated on the interface layer and cured at 100-150°C for 30-120 minutes to obtain a silicone rubber coating with high adhesion.

[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. Simple and Efficient One-Step Coating Process: This invention employs a one-step coating process, integrating multiple functions such as anti-sticking, self-exudation, and high adhesion into a single coating. This method significantly simplifies traditional multi-layer coating processes, greatly reducing production costs and time. Simultaneously, one-step coating also reduces interlayer interface problems, improving the overall performance and stability of the coating.

[0018] 2. Excellent anti-stick properties and self-oiling characteristics coexist: By introducing low molecular weight dimethyl silicone oil into the coating mixture, this invention successfully combines anti-stick properties and self-oiling characteristics. This unique combination enables the coating surface to not only have ultra-low adhesion, but also to quickly repair surface properties through a self-oiling mechanism in the event of wear or micro-damage, significantly extending the service life and reliability of the coating.

[0019] 3. High Adhesion and Wide Applicability to Substrates: The coating formulation of this invention takes into account the adhesion to substrates. By adjusting the ratio of PDMS prepolymer, hydrogen-containing silicone oil, and low molecular weight dimethyl silicone oil, and by employing appropriate substrate pretreatment methods, the coating can form strong bonds with a variety of substrates (such as metals, glass, ceramics, and polymer materials). This greatly expands the application range of the coating and meets the needs of different fields.

[0020] 4. Excellent High-Temperature Resistance: The organosilicon material used in this invention possesses excellent high-temperature resistance. Through a carefully designed curing process (curing at 60–150°C for 30–120 minutes), the coating forms a stable cross-linked network structure. This allows the coating to maintain its non-stick and self-exuding oil properties even under high-temperature environments, greatly expanding its application potential under harsh conditions, such as in high-temperature baking equipment and heat exchanger surface treatment. Attached Figure Description

[0021] To more clearly illustrate the technical solutions of the embodiments of this disclosure, the accompanying drawings of the embodiments will be briefly described below. It should be understood that the drawings described below only relate to some embodiments of this disclosure and are not intended to limit this disclosure, wherein: Figure 1 This is a comparison diagram of the ultra-low adhesion coating with anti-stick and self-oiling properties prepared on stainless steel according to Embodiment 1 of the present invention.

[0022] Figure 2 This is an AFM data graph of the stainless steel sheet sample prepared in Example 1 of the present invention and its adhesion results.

[0023] Figure 3 These are interference fringes of the oil film on the surface of the stainless steel sheet sample prepared in Example 2 of this invention.

[0024] Figure 4 This is a comparison diagram of the peel strength of the T-shaped 3M tape on the aluminum alloy sheet sample prepared in Example 4 of this invention.

[0025] Figure 5 This is the adhesion peeling effect on the glass slide adopted in Comparative Example 1 of the present invention, which adopts ASTM D3359. Detailed Implementation

[0026] To make the objectives, technical solutions, and advantages of the embodiments of this disclosure clearer, the technical solutions of the embodiments of this disclosure will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this disclosure. All other embodiments obtained by those skilled in the art based on the described embodiments of this disclosure without creative effort are also within the scope of protection of this disclosure.

[0027] Unless otherwise defined, all terms used herein (including technical and scientific terms) shall have the same meaning as commonly understood by one of ordinary skill in the art to which this subject matter pertains. It will be further understood that terms such as those defined in commonly used dictionaries shall be interpreted as having the meaning consistent with their meaning in the context of the specification and in the relevant art, and shall not be interpreted in an idealized or overly formal form unless otherwise explicitly defined herein. As used herein, the statement of “connecting” or “coupling” two or more parts together shall mean that these parts are directly joined together or joined through one or more intermediate components.

[0028] The term "embodiment" as used herein means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of the phrase "embodiment" in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0029] The present invention provides a method for preparing an ultra-low adhesion coating with anti-stick and self-oiling properties, comprising the following steps: Substrate pretreatment: Clean the surface of the substrate; use acetone, anhydrous ethanol and deionized water in sequence for ultrasonic cleaning for 5 to 15 minutes each time to remove surface oil and impurities, and dry in a clean environment for later use. In some embodiments of the present invention, the pretreatment process of the substrate may also employ plasma treatment or chemical immersion treatment. Chemical immersion treatment uses a 1% to 10% NaOH or HCl solution for 5 to 10 minutes. Preparation of coating mixture containing self-exuding oil components: Vinyl-terminated polydimethylsiloxane prepolymer, hydrogen-containing silicone oil, platinum catalyst and low molecular weight dimethyl silicone oil are mixed in proportion, and a uniform coating mixture is obtained after stirring. After vacuum degassing, a uniform coating mixture containing self-exuding oil components is obtained. The preferred mass ratio of the vinyl-terminated polydimethylsiloxane prepolymer to the hydrogen-containing silicone oil is 100:(8-12), for example, 100:8, 100:9, 100:10, 100:11, 100:12, and more preferably 100:10. The preferred mass fraction of the low molecular weight dimethyl silicone oil in the coating mixture is 30%-70%, for example, 30%, 40%, 50%, 60%, 70%, and more preferably 50%. The preferred molecular weight of the vinyl-terminated polydimethylsiloxane prepolymer is 5,000-20,000 g / mol, and the preferred average molecular weight is 8,000-15,000 g / mol, and more preferably 10,000 g / mol. The preferred hydrogen content of the hydrogen-containing silicone oil is 0.5-2.0 mmol / g, for example, 0.5 mmol / g, 0.8 mmol / g, 1.0 mmol / g, 1.5 mmol / g, 1.8 mmol / g, and more preferably ... The platinum content of the platinum catalyst is preferably 0.1-2 wt%, for example, 0.1 wt%, 0.5 wt%, 1.0 wt%, 1.5 wt%, 2.0 wt%, more preferably 0.5 wt%; the viscosity of the low molecular weight dimethyl silicone oil is preferably 5-200 cSt, and the average viscosity is preferably 50-150 cSt, more preferably 50 cSt. In this invention, the stirring temperature during the mixing process is preferably 20-40°C, for example, 20°C, 25°C, 30°C, 35°C, or 40°C; the stirring time is preferably 0.5-2 hours, for example, 0.5 hours, 1.0 hour, 1.5 hours, or 2 hours; the vacuum degree of vacuum degassing is 1-100 Pa; and the degassing time is preferably 10-60 minutes, for example, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, or 60 minutes. Applying an ultra-low adhesion self-exuding oil coating: After applying a coating mixture containing self-exuding oil components to the surface of a pretreated substrate, the substrate is placed in an oven and cured, preferably at 60–150°C, for 30–120 minutes. For example, the temperature can be 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C; for 30 minutes, 40 minutes, 60 minutes, 75 minutes, 90 minutes, or 120 minutes, forming an ultra-low adhesion coating with both anti-stick and self-exuding oil properties on the substrate surface. During the curing process, the temperature can be raised in stages for curing. Specifically, the curing temperature is raised first at 60-100℃ for 30-60 minutes, and then at 100-150℃ for 30-600 minutes.

[0030] In this invention, during the process of applying the coating mixture containing self-penetrating oil components to the surface of the pretreated substrate, the substrate is preferably degassed in a vacuum environment of 1~100Pa for 5~30 minutes before coating, for example, 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, or 30 minutes; the thickness of the coating after coating is preferably 5~100μm, for example, 5μm, 20μm, 45μm, 60μm, 75μm, 85μm, 90μm, or 100μm.

[0031] The ultra-low adhesion coating with anti-stick and self-oiling properties provided by this invention is used to improve the adhesion of silicone rubber coatings. The substrate can be glass, metal, ceramic or polymer material, and the silicone rubber material can be Sylgard® 184, Sylgard® 527, etc.

[0032] The following is an explanation with reference to specific embodiments: Example 1: A method for preparing an ultra-low adhesion coating with both anti-stick and self-oiling properties, the method comprising the following steps: S1: Substrate Pretreatment A stainless steel substrate measuring 200mm × 50mm × 2mm was selected as the experimental subject. The substrate was ultrasonically cleaned sequentially with acetone, anhydrous ethanol, and deionized water for 10 minutes each time to thoroughly remove surface oil and impurities. After cleaning, it was dried at room temperature in a clean environment for later use. Furthermore, to enhance the adhesion between the coating and the substrate, the dried glass substrate was placed in a plasma cleaner and treated with oxygen plasma for 5 minutes, or immersed in a 5% NaOH solution for 10 minutes. After treatment, it was thoroughly rinsed with deionized water and air-dried for later use.

[0033] S2: Preparation of coating mixture containing self-penetrating oil components Weigh 10g of vinyl-terminated polydimethylsiloxane prepolymer with a molecular weight of 10,000 g / mol. Weigh 1g of hydrogen-containing silicone oil with a hydrogen content of 1.0 mmol / g, making the mass ratio of PDMS prepolymer to hydrogen-containing silicone oil 100:10. Low molecular weight dimethyl silicone oil: Weigh 11g of low molecular weight dimethyl silicone oil with a viscosity of 50 cSt, making its mass fraction in the coating mixture 50%. Add an appropriate amount of platinum catalyst with a platinum content of 0.5 wt% (approximately 0.1g).

[0034] Place all the above components into a clean beaker and stir with a magnetic stirrer at 25°C for 1 hour until a homogeneous coating mixture is formed. Place the homogeneous coating mixture in a vacuum drying oven and degas for 30 minutes under a vacuum of 50 Pa to remove air bubbles from the mixture, thereby obtaining a coating mixture containing self-exuding oil components.

[0035] S3: Coated with an ultra-low adhesion self-adhesive coating The pretreated glass substrate was coated using a spin coating method. The coating mixture was dropped onto the center of the substrate, and the spin coating parameters were set as follows: initial speed of 500 rpm for 10 seconds to ensure uniform coating spread; then, the spin was maintained at 2000 rpm for 30 seconds, controlling the coating thickness to approximately 20 μm. After coating, the sample was placed in a vacuum environment (50 Pa) for 15 minutes to degas, further eliminating microbubbles in the coating and ensuring its density and smoothness.

[0036] The degassed sample was placed in an oven and cured at 100°C for 60 minutes. During the curing process, the hydrogen-containing silicone oil and PDMS prepolymer underwent an addition reaction under the action of a platinum catalyst, forming a cross-linked elastomer network. Simultaneously, low molecular weight dimethyl silicone oil was physically embedded within the network. After curing, the sample was removed and cooled to room temperature. At this point, an ultra-low adhesion coating with both anti-stick and self-exuding oil properties was formed on the substrate surface. The result was as follows: Figure 1 The following is a sample image of the steel sheet constructed according to the present invention. Figure 1 The image above shows PDMS without added silicone oil.

[0037] S4: Performance Evaluation Atomic force microscopy (AFM) was used to observe the morphology of the coating surface, revealing a smooth and flat surface with no obvious defects. Figure 2 The right side shows the AFM adhesion test result for sample 1, which is 15 nN, much smaller than... Figure 2 The PDMS sample on the left shows that it has excellent anti-adhesion properties.

[0038] Using a needle scraper to create tiny scratches on the coating surface, after standing for 1 hour, the scratches gradually disappeared, indicating that the low molecular weight dimethyl silicone oil migrated from the inside of the coating to the surface, achieving a self-healing function.

[0039] Example 2

[0040] S1: Substrate Pretreatment A 100mm × 100mm × 1mm 304 stainless steel sheet was selected as the experimental subject. The substrate was ultrasonically cleaned sequentially with acetone, anhydrous ethanol, and deionized water for 8 minutes each time to thoroughly remove surface oil and impurities. After cleaning, it was dried at room temperature in a clean environment for later use. To enhance the adhesion between the coating and the metal substrate, the dried stainless steel sheet was placed in a plasma cleaner and treated with argon plasma for 3 minutes. After treatment, it was rinsed with deionized water and air-dried for later use.

[0041] S2: Preparation of coating mixtures containing self-penetrating oil components Weigh 12g of vinyl-terminated polydimethylsiloxane prepolymer with a molecular weight of 15,000 g / mol. Weigh 1.2g of hydrogen-containing silicone oil with a hydrogen content of 1.5 mmol / g, making the mass ratio of PDMS prepolymer to hydrogen-containing silicone oil 100:10. Low molecular weight dimethyl silicone oil: Weigh 8g of low molecular weight dimethyl silicone oil with a viscosity of 100 cSt, making its mass fraction in the coating mixture 37.5%. Add 0.15g of platinum catalyst with a platinum content of 1 wt%.

[0042] Place all the above components into a clean beaker and stir with a magnetic stirrer at 30°C for 1.5 hours until a homogeneous coating mixture is formed. Place the homogeneous coating mixture in a vacuum drying oven and degas for 45 minutes under a vacuum of 20 Pa to remove air bubbles from the mixture.

[0043] S3: Coated with an ultra-low adhesion self-adhesive coating The pretreated stainless steel substrate was coated using a spraying method. A pneumatic spray gun was used, with a spraying pressure of 0.3 MPa and a spray distance of 15 cm, spraying evenly in a figure-eight pattern. The coating thickness was controlled to be approximately 50 μm. After coating, the sample was placed in a vacuum environment (vacuum degree of 30 Pa) for 20 minutes to degas and further eliminate microbubbles in the coating.

[0044] The degassed sample was placed in an oven and cured at 120°C for 90 minutes. After curing, the sample was removed and slowly cooled to room temperature. At this point, an ultra-low adhesion coating with both non-stick and self-exuding properties was formed on the stainless steel surface.

[0045] S4: Performance Evaluation Atomic force microscopy (AFM) was used to observe the morphology of the coating surface, revealing a smooth and flat surface with no obvious defects. The AFM adhesion test showed a value of 18 nN, significantly lower than... Figure 2 The PDMS sample on the left shows that it has excellent anti-adhesion properties.

[0046] Using a needle scraper, tiny scratches were made on the coating surface. After standing for 1.5 hours, the scratches gradually disappeared, indicating that the low molecular weight dimethyl silicone oil migrated from the interior of the coating to the surface, achieving a self-healing function. This was observed under an optical microscope. Figure 3 Thin-film interference fringes of the oil film are visible, indicating the presence of an extremely thin oil film on the sample surface.

[0047] Example 3: S1: Substrate Pretreatment A polycarbonate sheet measuring 80mm × 80mm × 3mm was selected as the experimental subject. The surface was gently wiped with a neutral detergent solution, then rinsed three times with deionized water. The surface was then gently wiped with a lint-free cloth dampened with anhydrous ethanol to remove residual stains. The sheet was then dried at room temperature in a clean environment for 30 minutes. To enhance the adhesion between the coating and the polymer substrate, the dried polycarbonate sheet was placed in a UV ozone cleaner for 2 minutes.

[0048] S2: Preparation of coating mixtures containing self-penetrating oil components Weigh 8 g of vinyl-terminated polydimethylsiloxane prepolymer with a molecular weight of 8,000 g / mol. Weigh 0.72 g of hydrogen-containing silicone oil with a hydrogen content of 0.8 mmol / g, making the mass ratio of PDMS prepolymer to hydrogen-containing silicone oil 100:9. Low molecular weight dimethyl silicone oil: Weigh 13 g of low molecular weight dimethyl silicone oil with a viscosity of 20 cSt, making its mass fraction in the coating mixture 60%. Add 0.08 g of platinum catalyst with a platinum content of 0.3 wt%.

[0049] Place all the above components into a clean beaker and stir with a magnetic stirrer at 25°C for 40 minutes until a homogeneous coating mixture is formed. Place the homogeneous coating mixture in a vacuum drying oven and degas for 25 minutes under a vacuum of 40 Pa to remove air bubbles from the mixture.

[0050] S3: Coated with an ultra-low adhesion self-adhesive coating The pretreated polycarbonate substrate was coated using a blade coating method. An automated coating machine was used, with the blade height set to 100 μm and the coating applied uniformly at a speed of 2 mm / s. The coating thickness was controlled to be approximately 30 μm. After coating, the sample was placed in a vacuum environment (50 Pa) for 10 minutes to degas and further eliminate microbubbles in the coating.

[0051] The degassed sample was placed in an oven and cured at 80°C for 120 minutes. After curing, the sample was removed and allowed to cool naturally to room temperature. At this point, an ultra-low adhesion coating with both anti-stick and self-oiling properties was formed on the polycarbonate surface.

[0052] S4: Performance Evaluation Atomic force microscopy (AFM) was used to observe the morphology of the coating surface, revealing a smooth and flat surface with no obvious defects. The AFM adhesion test showed a strength of 21.1 nN, significantly lower than that of the coating. Figure 2 The PDMS sample on the left shows that it has excellent anti-adhesion properties.

[0053] Using a needle scraper to create tiny scratches on the coating surface, after 1.5 hours of standing, the scratches gradually disappeared, indicating that the low molecular weight dimethyl silicone oil migrated from the inside of the coating to the surface, achieving a self-healing function.

[0054] Example 4: S1: Substrate Pretreatment A 6061 aluminum alloy sheet with dimensions of 70mm × 70mm × 2mm was selected as the experimental subject. The substrate was ultrasonically cleaned sequentially with acetone, anhydrous ethanol, and deionized water for 12 minutes each time to thoroughly remove surface oil and impurities. After cleaning, it was dried at room temperature in a clean environment for later use. Further, the dried aluminum alloy sheet was immersed in a 3% HCl solution for 8 minutes to enhance surface roughness and activity. After treatment, it was thoroughly rinsed with deionized water and dried in a 60℃ oven for 15 minutes for later use.

[0055] S2: Preparation of coating mixtures containing self-penetrating oil components Weigh 15g of vinyl-terminated polydimethylsiloxane prepolymer with a molecular weight of 12,000 g / mol. Weigh 1.65g of hydrogen-containing silicone oil with a hydrogen content of 1.2 mmol / g, making the mass ratio of PDMS prepolymer to hydrogen-containing silicone oil 100:11. Low molecular weight dimethyl silicone oil: Weigh 12g of low molecular weight dimethyl silicone oil with a viscosity of 80 cSt, making its mass fraction in the coating mixture 42%. Add 0.2g of platinum catalyst with a platinum content of 0.8 wt%.

[0056] Place all the above components into a clean beaker and stir with a mechanical stirrer at 35°C for 55 minutes until a homogeneous coating mixture is formed. Place the homogeneous coating mixture in a vacuum drying oven and degas for 50 minutes under a vacuum of 15 Pa to remove air bubbles from the mixture.

[0057] S3: Coated with an ultra-low adhesion self-adhesive coating The pretreated aluminum alloy substrate was coated using an dip-coating method. The substrate was immersed in the coating mixture at a speed of 5 mm / s, held for 5 seconds, and then withdrawn at the same constant speed. The coating thickness was controlled to be approximately 40 μm. After coating, the sample was placed in a vacuum environment (vacuum degree of 25 Pa) for 15 minutes to degas and further eliminate microbubbles in the coating.

[0058] The degassed sample was placed in an oven and cured at 110°C for 75 minutes. After curing, the sample was removed and cooled at room temperature for 30 minutes. At this point, an ultra-low adhesion coating with both anti-stick and self-oiling properties was formed on the aluminum alloy surface.

[0059] S4: Performance Evaluation Atomic force microscopy (AFM) was used to observe the morphology of the coating surface, revealing a smooth and flat surface with no obvious defects. The AFM adhesion test showed a strength of 13.7 nN, significantly lower than that of the coating. Figure 2 The PDMS sample on the left shows that it has excellent anti-adhesion properties.

[0060] The known sample was subjected to a T-peel test with 3M-VHB tape, such as... Figure 4 The peel force of Example 4 was measured to be 0.566 gf / cm, which is less than that of common materials such as PDMS (5.30 gf / cm) and polytetrafluoroethylene (26.7 gf / cm).

[0061] Example 5: S1: Substrate Pretreatment Alumina ceramic sheets measuring 60mm × 60mm × 5mm were selected as the experimental subjects. The substrate was ultrasonically cleaned sequentially with acetone, anhydrous ethanol, and deionized water for 15 minutes each time to thoroughly remove surface oil and impurities. After cleaning, the sheets were dried at 100℃ for 30 minutes in a clean environment. To enhance the adhesion between the coating and the ceramic substrate, the dried ceramic sheets were placed in a plasma cleaner and treated with oxygen plasma for 6 minutes. After treatment, they were rinsed with deionized water and dried in an oven at 80℃ for 20 minutes.

[0062] S2: Preparation of coating mixtures containing self-penetrating oil components Weigh 9 g of vinyl-terminated polydimethylsiloxane prepolymer with a molecular weight of 18,000 g / mol. Weigh 0.99 g of hydrogen-containing silicone oil with a hydrogen content of 1.8 mmol / g, making the mass ratio of PDMS prepolymer to hydrogen-containing silicone oil 100:11. Low molecular weight dimethyl silicone oil: Weigh 7 g of low molecular weight dimethyl silicone oil with a viscosity of 150 cSt, making its mass fraction in the coating mixture 41%. Add 0.12 g of platinum catalyst with a platinum content of 1.5 wt%.

[0063] Place all the above components into a clean beaker and stir with a mechanical stirrer at 28°C for 80 minutes until a homogeneous coating mixture is formed. Place the homogeneous coating mixture in a vacuum drying oven and degas for 60 minutes under a vacuum of 10 Pa to remove air bubbles from the mixture.

[0064] S3: Coated with an ultra-low adhesion self-adhesive coating The pretreated ceramic substrate was coated using screen printing. A 200-mesh polyester screen with a squeegee hardness of 70 degrees was used, with a printing pressure of 0.4 MPa and a printing speed of 100 mm / s. The coating thickness was controlled to be approximately 25 μm. After coating, the sample was placed in a vacuum environment (vacuum degree of 35 Pa) for 25 minutes to degas and further eliminate microbubbles in the coating.

[0065] The degassed sample was placed in an oven and cured at 135°C for 60 minutes. After curing, it was slowly cooled to room temperature at a rate of 1°C / min. At this point, an ultra-low adhesion coating with both anti-stick and self-oiling properties was formed on the ceramic surface.

[0066] S4: Performance Evaluation Atomic force microscopy (AFM) was used to observe the morphology of the coating surface, revealing a smooth and flat surface without obvious defects. The AFM adhesion strength was 17.3 nN, significantly lower than that of the coating. Figure 2 The PDMS sample on the left shows that it has excellent anti-adhesion properties.

[0067] The known sample was subjected to a T-peel test with 3M-VHB tape, such as... Figure 4 The peel force of Example 4 was measured to be 0.610 gf / cm, which is less than that of common materials such as PDMS (5.30 gf / cm) and polytetrafluoroethylene (26.7 gf / cm).

[0068] Using a needle scraper to create tiny scratches on the coating surface, after standing for 2 hours, the scratches gradually disappeared, indicating that the low molecular weight dimethyl silicone oil migrated from the inside of the coating to the surface, achieving a self-healing function.

[0069] Example 6: A method of using a silicone rubber surface layer with high adhesion: S1: Substrate surface pretreatment A steel substrate with dimensions of 200mm × 50mm × 2mm was selected as the experimental subject. The substrate was ultrasonically cleaned sequentially with acetone, anhydrous ethanol, and deionized water for 10 minutes each time to thoroughly remove surface oil and impurities. The dried glass substrate was then placed in a plasma cleaner and treated with oxygen plasma for 5 minutes to improve surface activity and enhance coating adhesion.

[0070] S2: Coated interface layer containing self-exuding oil components Weigh 10g of vinyl-terminated polydimethylsiloxane prepolymer with a molecular weight of 10,000 g / mol. Weigh 1g of hydrogen-containing silicone oil with a hydrogen content of 1.0 mmol / g, making the mass ratio of PDMS prepolymer to hydrogen-containing silicone oil 100:10. Weigh 5g of low molecular weight dimethylsiloxane oil with a viscosity of 50 cSt, making its mass fraction in the mixture 33%. Add 0.1g of platinum catalyst with a platinum content of 0.5 wt%. Place the above components in a clean beaker and stir at 25°C for 1 hour until a homogeneous coating mixture is formed. Place the mixture in a vacuum drying oven and degas for 30 minutes under a vacuum of 50 Pa to remove air bubbles from the mixture.

[0071] A spin coating method was used, where the coating mixture was dropped onto the center of the substrate. The spin coating parameters were set as follows: initial speed of 500 rpm for 10 seconds, followed by rotation at 2000 rpm for 30 seconds, controlling the coating thickness to approximately 20 μm. After coating, the sample was placed in a vacuum environment (vacuum degree of 50 Pa) for degassing for 15 minutes. The sample was then placed in an oven and cured at 100°C for 15 minutes to form an interface layer containing self-exuding oil components.

[0072] S3: Coated silicone rubber surface layer Take the silicone rubber material Sylgard® 184 and mix it with the curing agent at a mass ratio of 10:1. Stir thoroughly for 30 minutes until homogeneous. Apply the silicone rubber solution onto the cured interface layer, using a scraping method to control the coating thickness to approximately 50 μm. After coating, place the sample in a vacuum environment (vacuum degree of 50 Pa) for 20 minutes to degas and remove air bubbles from the coating. Place the sample in an oven and cure at 120°C for 60 minutes to form a silicone rubber surface layer with high adhesion.

[0073] S4: Performance Evaluation Adhesion test: According to ASTM D3359 standard, such as Figure 5 The adhesion test using the X-scratch method was performed on the right, and the result was 5B, indicating that the coating has excellent adhesion to the substrate.

[0074] Comparative Example 1: A silicone rubber coating method without an interface layer, performed according to the following steps: S1: Substrate surface pretreatment The same as step S1 in Example 6, is followed by cleaning and plasma treatment.

[0075] S2: Direct coating of silicone rubber surface layer Same as step S3 in Example 6. The silicone rubber solution is directly coated onto the pretreated substrate surface to a thickness of approximately 50 μm. Degas in a vacuum environment for 20 minutes. Curing is then performed at 120°C for 60 minutes to form a silicone rubber surface layer.

[0076] S3: Performance Evaluation Adhesion test: According to ASTM D3359 standard, such as Figure 5 The left-slash X test result was 2B, indicating severe coating peeling and poor adhesion.

[0077] In summary: By introducing an interface layer containing self-exuding oil components between the substrate and the silicone rubber surface layer (Example 6), the adhesion and peel strength of the silicone rubber coating were significantly improved. Compared with Example 6 and Comparative Example 1, the coating in Example 6 achieved a 5B grade in the adhesion test, indicating a stronger interfacial bond.

[0078] This method for preparing a highly adhesive silicone rubber surface layer is not only simple and easy to operate, but also eliminates the need for additional adhesives, reducing process steps and material costs. Applicable to various substrates such as glass, metals, ceramics, and polymers, this method has broad application prospects and can be used in fields such as biomedical devices, electronic packaging, and flexible sensors, significantly improving product reliability and lifespan.

[0079] The above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application.

Claims

1. The application of an ultra-low adhesion coating with anti-stick and self-oiling properties in improving the adhesion of silicone rubber coatings, characterized in that, An ultra-low adhesion coating with anti-stick and self-oiling properties is introduced between the substrate and the silicone rubber coating; Preparation of coating mixture containing self-exuding oil components: Vinyl-terminated polydimethylsiloxane prepolymer, hydrogen-containing silicone oil, platinum catalyst and low molecular weight dimethyl silicone oil are mixed in proportion, and a uniform coating mixture is obtained after stirring. After vacuum degassing, a uniform coating mixture containing self-exuding oil components is obtained. The coating mixture is applied to the pretreated substrate surface with a coating thickness of 5–50 μm. After degassing under a vacuum of 1–100 Pa for 5–30 minutes, it is cured at 60–150 °C for 1–15 minutes to obtain an interface layer containing self-exuding oil components. Subsequently, a silicone rubber material with a thickness of 5–100 μm is coated on the interface layer and cured at 100–150 °C for 30–120 minutes to obtain a silicone rubber coating with high adhesion.

2. The application of the ultra-low adhesion coating with anti-stick and self-oiling properties as described in claim 1 in improving the adhesion of silicone rubber coatings, characterized in that, During the substrate pretreatment process, the substrate is ultrasonically cleaned sequentially with acetone, anhydrous ethanol, and deionized water for 5 to 15 minutes each time to remove surface oil and impurities. After cleaning, it is dried in a clean environment for later use.

3. The application of the ultra-low adhesion coating with anti-stick and self-oiling properties as described in claim 1 in improving the adhesion of silicone rubber coatings, characterized in that, In the process of preparing the coating mixture containing self-penetrating oil components, the vinyl-terminated polydimethylsiloxane prepolymer and the hydrogen-containing silicone oil are mixed at a mass ratio of 100:(8-12). After adding a small amount of platinum catalyst and mixing evenly, the low molecular weight dimethyl silicone oil is added. The mass fraction of the low molecular weight dimethyl silicone oil in the coating mixture is 30%-70%. The vinyl-terminated polydimethylsiloxane prepolymer has a molecular weight of 5,000–20,000 g / mol; the hydrogen content of the hydrogen-containing silicone oil is 0.5–2.0 mmol / g; the platinum content of the platinum catalyst is 0.1–2 wt%; and the viscosity of the low molecular weight dimethylsiloxane oil is 5–200 cSt.

4. The application of the ultra-low adhesion coating with anti-stick and self-oiling properties according to claim 1 in improving the adhesion of silicone rubber coatings, characterized in that, In the process of preparing the coating mixture containing self-penetrating oil components, the stirring temperature is 20-40℃, the stirring time is 0.5-2 hours, the vacuum degree of vacuum degassing is 1-100 Pa, and the degassing time is 10-60 minutes.

5. The application of the ultra-low adhesion coating with anti-stick and self-oiling properties according to claim 1 in improving the adhesion of silicone rubber coatings, characterized in that, The coating method used in the process of applying the ultra-low adhesion self-oiling coating is one of the following: spin coating, spray coating, scraping coating, dip coating or screen printing. During the process of applying the coating mixture containing self-penetrating oil components to the surface of the pretreated substrate, the substrate is placed in an environment with a vacuum degree of 1~100Pa for degassing for 5~30 minutes before coating; the thickness of the coating after coating is 5~100μm.

6. The application of the ultra-low adhesion coating with anti-stick and self-oiling properties as described in claim 1 in improving the adhesion of silicone rubber coatings, characterized in that, The substrate material is one of stainless steel, aluminum alloy, glass, ceramic, silicon wafer, polycarbonate, polypropylene, or polyimide.

Citation Information

Patent Citations

  • Lubricating organic-silicon anti-icing coating prepared by ''one-step method'' and preparation method of coating

    CN108587453A